Synthesis of large area AB stacked bilayer graphene by SiC epitaxy and transfer - Alsalman, Hussain; Hwang, Jeonghyun; Kim, Moonkyung; Campbell, Dorr; Kwak, Joon Young; Calderon, Brian; Ji, Yanxin; Gorantla, Sandeep; Bachmatiuk, Alicja; Ruemmeli, Mark H.; Spencer, Michael G. (IOP PUBLISHING LTD, 2018)
The dry transfer of AB stacked bilayer high quality SiC epitaxial graphene is presented. Monolayers were also transferred for comparison. Large continuous layers exceeding hundreds of microns were successfully transferred. Structural characterization, using Raman and TEM methods, are used to assess the uniformity and the quality of the transferred layers, in which case they are found to be of high quality and tight uniformity. The bilayer structural characterization methods indicate AB stacking with good uniformity and stacking order over large areas. Electrical characterization is used to extract mobility performance figures and other electrical characteristics for the transferred layers in which the bilayers distinctively show electrical characteristics akin to AB stacking in contrast to the transferred monolayers using the same methods. Contact resistance values as well as transfer length ratios are measured using TLM method and reported for bilayers. Finally, annealing studies show mobility enhancement for bilayers as well as potential application in gas sensing.
Keywords: RAPID SYNTHESIS; HIGH-QUALITY; GROWTH; LAYER; PERFORMANCE; TRANSISTORS; BANDGAP; OXYGEN; GAS